2017
DOI: 10.1097/meg.0000000000000891
|View full text |Cite
|
Sign up to set email alerts
|

Chronic comorbidities associated with inflammatory bowel disease: prevalence and impact on healthcare costs in Switzerland

Abstract: We found a considerably high prevalence of concomitant chronic diseases in IBD patients. This was associated with considerably higher healthcare costs, especially in the outpatient setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(38 citation statements)
references
References 49 publications
2
35
0
1
Order By: Relevance
“… 33 Type 2 diabetes and inflammatory bowel disease have been shown to share inflammatory pathways, 34 although large population based studies have not reported an association between these two diseases. 35 Nevertheless, we rigorously assessed the effect of possible residual confounding in several analyses; these analyses yielded consistent findings. Moreover, the null association observed with insulin (a last line treatment of which the users are typically at an advanced disease stage) as a negative control provides reassurance on the internal validity of our findings.…”
Section: Discussionmentioning
confidence: 90%
“… 33 Type 2 diabetes and inflammatory bowel disease have been shown to share inflammatory pathways, 34 although large population based studies have not reported an association between these two diseases. 35 Nevertheless, we rigorously assessed the effect of possible residual confounding in several analyses; these analyses yielded consistent findings. Moreover, the null association observed with insulin (a last line treatment of which the users are typically at an advanced disease stage) as a negative control provides reassurance on the internal validity of our findings.…”
Section: Discussionmentioning
confidence: 90%
“…The prevalence of comorbidities in our study was relatively low compared with other studies. [14][15][16] A plausible explanation might be that the median age of study patients was relatively young (approximately 44 years old). Another reason could be that many IBD specialists or even patients are reluctant to use biologic Open access therapy, and we cannot discard a possible overlap between comorbidities and EIMs due to the retrospective study design.…”
Section: Discussionmentioning
confidence: 99%
“…13 The prevalence of comorbidities in patients with IBD ranges between 30% and 70%. [14][15][16] The presence of comorbidities in patients with IBD has been shown to negatively affect patients' HRQoL, 16 and importantly to prolong their length of hospital stay and increase the risk of postsurgical mortality. Furthermore, immune-mediated inflammatory disorders associated with IBD have been proven to incur higher healthcare costs.…”
Section: What Are the New Findings?mentioning
confidence: 99%
See 1 more Smart Citation
“…Both are chronic diseases that are associated with increased risk of cardiovascular disease and premature mortality ( 33 , 34 ). Despite the potential overlaps, earlier studies have not been able to demonstrate a higher risk of diabetes in patients with inflammatory bowel disease ( 35 38 ). However, in a recent study from the UK, the prevalence of clinical inflammatory bowel disease in adult individuals with type 1 diabetes was ~6-fold higher compared to non-diabetic controls (1.5 vs. 0.3%, respectively) ( 39 ).…”
Section: Gastrointestinal Manifestations In Patients With Diabetesmentioning
confidence: 95%